Teachers` implementation of Inclusive Education in Ghanaian primary schools: An insight into government policy and practice. - Alhassan, Awal Mohammed (Advances in Social Sciences Research Journal, 2014)
The study reported in this paper is the examination of teachers’ experiences of the implementation of Inclusive Education in two districts in Ghana, Bole in the north and New Juabeng in the south in ten primary and junior secondary schools. Using the framework of Ntombela (2009, 2011) and Torombe (2013) this article replicates their study in new setting - Ghana. Employing both quantitative and qualitative data analyses procedures, the study found that teachers had limited, varied and often distorted understandings of the inclusive policy and the innovation. These understandings suggested that instead of the paradigm shift warranted by the new policy, most of the teachers still relied heavily on the old deficit, medical model of educating learners with special educational needs. The study concludes that, to be successful, the policy initiation process needs to become clear and more inclusive to enable stakeholders to embrace the agenda and to understand its purpose. Further, a new policy will not be able to challenge and change the culture and practice in schools unless teachers are well trained and the necessity of appropriate allocation and use of resources put in place. Keywords: Ghana, educational innovation, Inclusive Education, special education needs, policy dissemination.